Guppy (Poecilia reticulata Peters, 1859). - Gama, M. (2020)
This document has been produced in 2020 within the framework of the LIFE INVASAQUA project (LIFE17 GIE/ES/000515) Aquatic Invasive Alien Species of Freshwater and Estuarine Systems: Awareness and Prevention in the Iberian Peninsula, funded by the European Commission LIFE program.